2023
DOI: 10.1002/biot.202200521
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of ethylene glycol to glycolic acid by Yarrowia lipolytica: A route for poly(ethylene terephthalate) (PET) upcycling

Abstract: Biological recycling of PET waste has been extensively investigated recently to tackle plastic waste pollution, and ethylene glycol (EG) is one of the main building blocks recovered from this process. Wild-type Yarrowia lipolytica IMUFRJ 50682 can be a biocatalyst to biodepolymerize PET. Herein, we report its ability to perform oxidative biotransformation of EG into glycolic acid (GA): a higher value-added chemical with varied industrial applications. We found that this yeast tolerates high EG concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…150 On the other hand, Kim et al used chemoenzymatic hydrolysis technology to obtain EG (30.6 g L −1 ) from PET, which was subsequently converted to 31.4 g L −1 of GA with a molar yield of 91.6% for G. oxydans. Carniel et al 233 demonstrated the ability of Y. lipolytica strain IMUFRJ 50682 to biotransform reagent-grade EG into GA (430 mM), at a molar yield of 78.1% after 72 h. This yeast is also capable to biodepolymerize PET, 216 so EG released in this process could be concomitantly converted into GA by the same biocatalyst.…”
Section: Upcycling Of Egmentioning
confidence: 99%
See 3 more Smart Citations
“…150 On the other hand, Kim et al used chemoenzymatic hydrolysis technology to obtain EG (30.6 g L −1 ) from PET, which was subsequently converted to 31.4 g L −1 of GA with a molar yield of 91.6% for G. oxydans. Carniel et al 233 demonstrated the ability of Y. lipolytica strain IMUFRJ 50682 to biotransform reagent-grade EG into GA (430 mM), at a molar yield of 78.1% after 72 h. This yeast is also capable to biodepolymerize PET, 216 so EG released in this process could be concomitantly converted into GA by the same biocatalyst.…”
Section: Upcycling Of Egmentioning
confidence: 99%
“…To the best of our knowledge, only the bacterium I. sakainesis ( produces PHA) and yeast Y. lipolytica ( produces GA) have been reported with this ability so far. 125,233 Thus, synthetic biology is a crucial tool to diversify the variety of final products, by constructing metabolic pathways containing specific enzymes from different organism sources to catalyze sequential reactions. The choice of microbial chassis for expressing these metabolic pathways must take into account several factors: source of heterologous enzymes, monomer uptake capability, and tolerance to moderate to high monomer and product concentrations, inability to consume final product, among others.…”
Section: Integration Of Process Steps For Pet Upcyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the applicability of the fusion enzyme catalysis in bioremediation we performed a reaction scale-up exploiting a strain of E. coli BL21 (DE3) cells transformed with the pET-28-a-CYP116B5-SOX(+) vector: E. coli (CYP116B5-SOX). We employed the transformed bacteria as biocatalytic system to remove tamoxifen, [64][65][66][67][68][69][70][71][72][73] commonly reported as water pollutant, [9] from an aqueous buffered medium, taken as a model of contaminated water. We used HPLC-MS to identify the metabolites produced by CYP116B5-SOX catalysis.…”
Section: Drugs Bioconversion Using Cyp 116b5-sox Expressing E Coli St...mentioning
confidence: 99%